2018
DOI: 10.4103/ijpvm.ijpvm_100_17
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Effect of Different Fractions Obtained from Teucrium polium Hydroalcoholic Extract in Rats

Abstract: Background:This study was aimed to screen the antihyperlipidemic effect of different fractions of Teucrium polium to obtain the most efficient herbal fraction for isolation of bioactive constituents responsible for hypolipidemic activity.Methods:Chloroform, butanol, and aqueous fractions were obtained from hydroalcoholic extract of T. polium aerial parts using partitioning process. To induce hyperlipidemia, dexamethasone (Dex) was injected 10 mg/kg/day (s.c.) for 8 days. In the test groups, animals received 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Thus, we herein report that TP extract can cause a dramatic toxic effect on the embryo at 3 days of incubation, since ~95% of our TP-exposed embryos die after 3 days of treatment; therefore, it is clear that TP extract severely affects the survival probability of the exposed embryos in comparison with their controls. These data are consistent with several investigations related to the toxic effect of TP extract in animal models [17][18][19]. Moreover, our study revealed that TP extract could harm the chicken embryo and inhibit angiogenesis of CAM by ~40% after 2-4 days of exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we herein report that TP extract can cause a dramatic toxic effect on the embryo at 3 days of incubation, since ~95% of our TP-exposed embryos die after 3 days of treatment; therefore, it is clear that TP extract severely affects the survival probability of the exposed embryos in comparison with their controls. These data are consistent with several investigations related to the toxic effect of TP extract in animal models [17][18][19]. Moreover, our study revealed that TP extract could harm the chicken embryo and inhibit angiogenesis of CAM by ~40% after 2-4 days of exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The outcome of TP extract on women' s health is not well understood, especially during pregnancy. However, a few-existing data regarding the effect of TP extract on human health indicate that TP could be harmful during the early stage of normal fetal development, especially since it can induce hepatotoxicity in humans as well as in animal models [11,12,[17][18][19]. This is particularly important since pregnant women, especially in the Mediterranean region, might consume this medicinal plant without being aware of its adverse effects on their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…39 The leaves are slightly peppery and were commonly used to prepare tea and to spice up salads and goat cheeses. 39 Several studies have demonstrated certain pharmacological effects of T. polium as an antioxidant agent, 24 antibacterial, 40 antinociceptive, 41 antispasmodic, 42 antidiabetic, 43 diuretic, 44 hypolipidemic, 45 antifungal, 46 and cytotoxic. 47…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…For example, a hydroalcoholic extract of T. polium from Iran was tested on dexamethasone-induced hyperlipidemic rats. 51 The results of this investigation demonstrated that T. polium had a potent antihyperlipidemic effect by reducing the levels of TG, TC, and LDL-C and by increasing HDL-C levels. In addition, the hypolipidemic impact of streptozotocin-induced diabetic rats in Palestinian Teucrium leucocladum was also studied by Bassalat et al.…”
Section: Discussionmentioning
confidence: 68%